The University and Manpower Planning: A Re-Examination of the Issues in the Light of Changing Economic Conditions and New Developments in Labour Market Information - Skolnik, Michael L. (Canadian Journal of Higher Education, 1983)
The search for effective public policy approaches for relating higher education to the needs of the labour market was a subject of much attention in the 1960s and early 1970s, and the verdict was largely against centralized comprehensive manpower planning. This paper re-examines the role of manpower planning in the university sector, in light of new economic imperatives and new data production initiatives by Employment and Immigration Canada. It concludes by rejecting what is conventionally referred to as manpower planning, and offering, instead, a set of guidelines for improving the linkage between universities and the labour market within the framework of existing institutional and policy structures.